Does learning in clinical context in anatomical sciences improve examination results, learning motivation, or learning orientation?. Issue 1 (3rd June 2013) - Böckers, Anja; Mayer, Christian; Böckers, Tobias Maria
<x xml:space="preserve">Abstract</x> The preclinical compulsory elective course "Ready for the Operating Room (OR)!?" [in German]: "Fit für den OP (FOP)"] was implemented for students in their second year, who were simultaneously enrolled in the gross anatomy course. The objective of the study was to determine whether the direct practical application of anatomical knowledge within the surgical context of the course led to any improvement in learning motivation, learning orientation, and ultimately examination results in the gross anatomy course, as compared with a control group. Within the scope of five teaching sessions, the students learned surgical hand disinfection, suturing techniques, and the identification of commonly used surgical instruments. In addition, the students attended five surgical demonstrations performed by surgical colleagues on cadavers. Successful learning of these basic skills was then assessed based on an Objectively Structured Practical Examination. Learning motivation and learning orientation in both subgroups was determined using the SELLMO‐ST motivation test and the Approaches and Study Skills Inventory test. While a significant increase in work avoidance was identified in the control group, this was not the case for FOP participants. Similarly, an increase in the "deep approach" to learning, as well as a decrease in the "surface approach, " was able to be documented among the FOP participants following completion of the course. The results suggest that students enrolled in the gross anatomy course, who were simultaneously provided with the opportunity to learn in clinical context, were more likely to be successful at maintaining learning motivation and learning orientation required for the learning process, than students who attended the gross anatomy course alone. Anat Sci Educ. 7: 3–11. © 2013 American Association of Anatomists.